2021
DOI: 10.18502/cmm.7.2.7032
|View full text |Cite
|
Sign up to set email alerts
|

Non-Candida albicans Candida Species: Virulence Factors and Species Identification in India

Abstract: Background and Purpose: The predominant cause of candidiasis was Candida albicans which has recently changed to non-Candida albicans Candida (NCAC) (i.e., Candida spp. other than the C. albicans). The NCAC spp., earlier considered non-pathogenic or minimally virulent, are now considered a primary cause of morbidity and mortality in immunocompromised individuals. Given the NCAC spp.has become more common in clinical cases, this study aimed to determine the prevalence of NCAC spp. in different clinical specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Our results coincide with two available studies on the epidemiology of Candida in Honduras [ 20 , 25 ] in which C. albicans is described as the predominant yeast in urine and sputum. Similarly, our results are also similar to those previously reported elsewhere [ 32 , 34 , 35 ]. The clinical significance of yeasts in urine and sputum is still not entirely clear, as it could indicate contamination, commensalism, colonization, or even a localized infection that could later evolve into a disseminated infection [ 20 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results coincide with two available studies on the epidemiology of Candida in Honduras [ 20 , 25 ] in which C. albicans is described as the predominant yeast in urine and sputum. Similarly, our results are also similar to those previously reported elsewhere [ 32 , 34 , 35 ]. The clinical significance of yeasts in urine and sputum is still not entirely clear, as it could indicate contamination, commensalism, colonization, or even a localized infection that could later evolve into a disseminated infection [ 20 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…positive reaction, -: negative reaction, *: strain variation The results of this test were the same as those of Hedayati, et al [37] in which the data showed that Candida species were accurately identified using the HiCandida identification kit, which is also conforms to Singh, et al [38] who stated that Identification was accomplished with the support of diagnostic by using this kit.…”
Section: Biochemical Testsupporting
confidence: 77%
“…However, a lot of research publications discuss the development of virulence among NAC species. [38][39][40] The demonstration of virulence factors shows that 43 (61.43%) isolates showed phospholipase activity and 25 isolates of C.tropicalis showed maximum phospholipase activity. These results were correlated with the study findings of Sachin C et al which showed that 60.9% of isolates demonstrated phospholipase activity and 76% and phospholipase activity was predominantly produced by 19 isolates of C. tropicalis.…”
Section: Discussionmentioning
confidence: 99%